Econometric Modelling on Happiness in Learning Mathematics: The Case of Senior High Students - Casinillo, Leomarich F; Casinillo, Emily L. (Universitas Negeri Semarang, 2020)
This study developed econometric models on the students’ happiness in learning mathematics to identify its influencing factors. A complete enumeration of 115 grade 11 students in the Visayas State University were employed as participants. Results showed that about 61% of the students considered themselves as moderately happy in learning. Their expected happiness is approximately the same with their actual happiness, which is one of the significant determinants in the models. STEM students among other strands in senior high school are more likely happy learners. Household income, allowance, and mental health condition show a small influence on their happiness in learning. Students who spend more time in the library, and those living in rural places tend to be happy in learning. Furthermore, physical health condition shows an inverse effect on students’ well-being in learning mathematics, while social relationships and the distance from home to school do not contribute to their happiness. Abstrak Penelitian ini mengembangkan model ekonometrik pada kebahagiaan siswa dalam pembelajaran matematika untuk mengidentifikasi faktor-faktor yang memengaruhinya. Data diambil dari 115 mahasiswa kelas 11 di Universitas Negeri Visayas. Hasilnya menunjukkan bahwa sekitar 61% mahasiswa menilai diri mereka relatif bahagia. Tingkat kebahagiaan yang mereka harapkan relatif sama dengan yang mereka tunjukkan secara aktual dan ini merupakan salah satu model yang signifikan buktinya. Siswa yang mengikuti program STEM dan sejenisnya pada jenjang sekolah menengah atas (SMA) tampak lebih bahagia. Pendapatan di rumah, tunjangan, dan kesehatan mental tampak menunjukkan pengaruh yang tidak seberapa pada kebahagiaan belajar. Sementara itu siswa yang menghabiskan banyak waktu di perpustakaan dan tinggal di perdesaan cenderung bahagia dalam belajar. Lebih lanjut, kondisi kesehatan fisik tampak berbanding terbalik dengan kesejahteraan siswa dalam belajar matematika, sementara itu relasi sosial dan jarak rumah ke sekolah tidak berkontribusi pada kebahagiaan siswa.